The Taxation of Bilateral Trade with Endogenous Information - Tri Vi Dang; Florian Morath (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper analyzes the effects of taxation on information acquisition and bilateral trade in decentralized markets. We show that a profit tax and a transaction tax have opposite implications for equilibrium outcome in bargaining. A marginal increase of a transaction tax increases the incentive to produce private information which creates adverse selection and reduces the probability of trade. In contrast, a marginal increase of a profit tax reduces the incentive to produce information and increases the probability of trade. In markets where there are gains from trade and private information acquisition creates endogenous lemons problems a profit tax dominates a transaction tax.
Keywords: C78; D82; D83; G18; H20; 330; bargaining; information acquisition; taxation; financial transaction tax; funding markets